The Effect of Emotional Intelligence and Self-Efficacy on Job Satisfaction in PT Gong Muke Craft Employees - Nur Fahdila; Agi Syarif Hidayat (Interdisciplinary Social Studies, 2026)
Job satisfaction serves as a critical determinant of workforce performance and loyalty, particularly within labor-intensive industries characterized by repetitive tasks and emotional demands. This study examines the influence of emotional intelligence and self-efficacy on job satisfaction among employees of PT Gong Muke Craft, a rattan craft manufacturing company in Indonesia. Grounded in Bandura's Social Cognitive Theory, this research addresses a notable gap in understanding psychological factors affecting manual craft workers, a population distinct from those in formal service or educational sectors. Employing a quantitative approach with causal associative design, data were collected through census sampling from 110 employees using validated questionnaires. Multiple regression analysis revealed that emotional intelligence exerted a positive and significant effect on job satisfaction (B = 0.166, p = 0.018), whereas self-efficacy demonstrated no significant partial influence (B = 0.103, p = 0.181). Nonetheless, both variables collectively contributed significantly to job satisfaction (F = 10.460, p = 0.000), explaining 16.4% of the variance. These findings underscore the predominant role of emotional regulation over self-confidence beliefs in shaping job satisfaction within routine-based manual work environments. Practically, this research recommends emotion-focused training interventions to enhance employee wellbeing and reduce turnover intentions in craft industries.